Multiple single-element transducer photoacoustic computed tomography system - Kalva, Sandeep Kumar (2018)
Light absorption by the chromophores (hemoglobin, melanin, water etc.) present in any biological tissue results in local temperature rise. This rise in temperature results in generation of pressure waves due to the thermoelastic expansion of the tissue. In a circular scanning photoacoustic computed tomography (PACT) system, these pressure waves can be detected using a single-element ultrasound transducer (SUST) (while rotating in full 360° around the sample) or using a circular array transducer. SUST takes several minutes to acquire the PA data around the sample whereas the circular array transducer takes only a fraction of seconds. Hence, for real time imaging circular array transducers are preferred. However, these circular array transducers are custom made, expensive and not easily available in the market whereas SUSTs are cheap and readily available in the market. Using SUST for PACT systems is still cost effective. In order to reduce the scanning time to few seconds instead of using single SUST (rotating 360° ), multiple SUSTs can be used at the same time to acquire the PA data. This will reduce the scanning time by two-fold in case of two SUSTs (rotating 180° ) or by four-fold and eight-fold in case of four SUSTs (rotating 90° ) and eight SUSTs (rotating 45° ) respectively. Here we show that with multiple SUSTs, similar PA images (numerical and experimental phantom data) can be obtained as that of PA images obtained using single SUST.